1996
DOI: 10.1002/mrm.1910360304
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved contrast‐enhanced 3D MR angiography

Abstract: An MR angiographic technique, referred to as 3D TRICKS (3D time-resolved imaging of contrast kinetics) has been developed. This technique combines and extends to 3D imaging several previously published elements. These elements include an increased sampling rate for lower spatial frequencies, temporal interpolation of k-space views, and zero-filling in the slice-encoding dimension. When appropriately combined, these elements permit reconstruction of a series of 3D image sets having an effective temporal frame r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
531
0
8

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 836 publications
(541 citation statements)
references
References 23 publications
2
531
0
8
Order By: Relevance
“…Recently, timeresolved CE-MRA methods with temporal update rates of the order of seconds have been introduced (3,4), and a number of studies have shown their potential for providing detailed information on vascular geometry without the need for exact bolus timing (5)(6)(7).…”
Section: Contrast-enhanced (Ce) Mr Angiography (Mra) Is An Establishementioning
confidence: 99%
“…Recently, timeresolved CE-MRA methods with temporal update rates of the order of seconds have been introduced (3,4), and a number of studies have shown their potential for providing detailed information on vascular geometry without the need for exact bolus timing (5)(6)(7).…”
Section: Contrast-enhanced (Ce) Mr Angiography (Mra) Is An Establishementioning
confidence: 99%
“…More recent developments in MRA include the application of view sharing techniques such as timeresolved imaging of contrast kinetics (TRICKS) and time-resolved echo-shared angiography technique (TREAT) (7,8) as well as image acceleration techniques such as generalized autocalibrating partially parallel acquisitions (GRAPPA) (9) or sensitivity encoding (SENSE) (10), which enable for fast CE-MRA acquisitions and time-resolved MRA (tr-CE-MRA) (7). Although CE-MRA and CTA are less invasive, both methods exclusively depict vessel morphology and geometry but do not provide information about the effect of vascular pathologies on local blood flow characteristics.…”
mentioning
confidence: 99%
“…[3] can be further refined using the following observations: i) For MRA images of the lower extremity, we can split the image vertically into right and left halves and assess the image quality for each half separately, i.e., Q (I) ϭ Q (Left part of I) ϩ Q (Right part of I). ii) Because of this similarity between adjacent horizontal scan lines, we can use every fourth or eighth scan line to evaluate image quality, which gives a result very close to that evaluated at every scan line but increases the computation efficiency by 4-or 8-fold (Fig.…”
Section: Quantify Image Qualitymentioning
confidence: 99%
“…Among data acquisition techniques for CEMRA, the time-resolved strategy offers a very useful option for many situations because of the elimination of the cumbersome timing of imaging to the contrast bolus arrival (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The time-resolved CEMRA generates time series images in a manner similar to fluoroscopic X-ray angiography, where image postprocessing has been used frequently to improve vasculature display (14,15).…”
mentioning
confidence: 99%